PENGARUH KOMPETENSI MOTIVASI KERJA DAN KEPUASAN KERJA TERHADAP PRODUKTIVITAS KERJA GURU PADA SMK NEGERI 1 GIANYAR KABUPATEN GIANYAR - Wijayanthi, Ni Putu Putri Ayu; Widya Goca, I Gusti Putu Agung; Dewi, Dewa Ayu Pani Tika (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Ngurah Rai, 2023)
Productivity is important for a teacher, because teachers must be productive in teaching and always develop the learning process. There is a problem of competence, work motivation and job satisfaction to improve the productivity of teachers SMK Negeri 1 Gianyar Gianyar Regency, so this research is very likely to know in detail the effect of competence, work motivation and job satisfaction with the productivity of teachers SMK Negeri 1 Gianyar Gianyar Regency. This study is intended to analyze the simultaneous and partial influence of competence, work motivation and job satisfaction of teachers of SMK Negeri 1 Gianyar Gianyar Regency. The sample size was determined using saturated sampling technique with a total of 67 teachers of SMK Negeri 1 Gianyar Gianyar Regency were included. Data analysis using classical hypothesis testing, multiple statistical calculations, calculation of determination, hypothesis testing. The results of the analysis concluded that there is a relationship direction simultaneously and individually between competence, work motivation and job satisfaction with teacher work productivity in SMK Negeri 1 Gianyar Regency.